Effectiveness of cuticular transpiration barriers in a desert plant at controlling water loss at high temperatures. (18th August 2015) - Schuster, Ann-Christin; Burghardt, Markus; Alfarhan, Ahmed; Bueno, Amauri; Hedrich, Rainer; Leide, Jana; Thomas, Jacob; Riederer, Markus
Abstract : Maintaining the integrity of the cuticular transpiration barrier even at elevated temperatures is of vital importance for hot-desert plants. We studied the effect of temperature on the leaf cuticular permeability of Rhazya stricta, an evergreen shrub from the Arabian Desert. Permeability increased 2.4-fold from 15° to 50°C which is much less than in all other species studied so far. We propose that high amounts of pentacyclic triterpenoids (85.2% of total wax) act as fillers mechanically stabilizing the cuticle and, thus, preventing thermal disruption of the cuticular transpiration barrier. Abstract: Maintaining the integrity of the cuticular transpiration barrier even at elevated temperatures is of vital importance especially for hot-desert plants. Currently, the temperature dependence of the leaf cuticular water permeability and its relationship with the chemistry of the cuticles are not known for a single desert plant. This study investigates whether (i) the cuticular permeability of a desert plant is lower than that of species from non-desert habitats, (ii) the temperature-dependent increase of permeability is less pronounced than in those species and (iii) whether the susceptibility of the cuticular permeability barrier to high temperatures is related to the amounts or properties of the cutin or the cuticular waxes. We test these questions with Rhazya stricta using the minimum leaf water vapour conductance ( g  min ) as a proxy for cuticular water permeability. g  min of R. stricta (5.41 × 10 −5 m s −1 at 25 °C) is in the upper range of all existing data for woody species from various non-desert habitats. At the same time, in R. stricta, the effect of temperature (15–50 °C) on g  min (2.4-fold) is lower than in all other species (up to 12-fold). Rhazya stricta is also special since the temperature dependence of g  min does not become steeper above a certain transition temperature. For identifying the chemical and physical foundation of this phenomenon, the amounts and the compositions of cuticular waxes and cutin were determined. The leaf cuticular wax (251.4 μg cm −2 ) is mainly composed of pentacyclic triterpenoids (85.2% of total wax) while long-chain aliphatics contribute only 3.4%. In comparison with many other species, the triterpenoid-to-cutin ratio of R. stricta (0.63) is high. We propose that the triterpenoids deposited within the cutin matrix restrict the thermal expansion of the polymer and, thus, prevent thermal damage to the highly ordered aliphatic wax barrier even at high temperatures.